Tweeting on Presidential Coattails: Congressional Candidate Use of Twitter in the 2020 Elections - Evan Crawford; Mikaela Foehr; Nathaniel Yee (Journal of Quantitative Description: Digital Media)
There is a long history of political science research focused on congressional candidates riding presidential coattails into office. The underlying theory for this potential relationship is relatively simple—when presidential nominees are popular, they can help bolster the electoral fortunes of their down-ballot, co-partisan candidates. If this is right, congressional candidates should be incentivized to publicly align themselves with their co-partisan presidential nominee, albeit in strategic ways. We look for this relationship by constructing an original dataset of congressional candidate Twitter data and identifying the extent to which candidates mention presidential nominees during the 2020 campaign, a behavior we call “tweeting on coattails.” Our data allow us to describe relationships between “tweeting on coattails”, candidate party ID, and district-level electoral conditions. We find that overall, challengers tweeted more than incumbents, but incumbents were more likely to “tweet on coattails.” In addition, candidates of both parties “tweeted on coattails” more frequently if they were running in a district where their party’s nominee is popular. This relationship was not symmetric in magnitude, however, as Republicans were significantly more likely to tweet about Donald Trump than Democrats were to tweet about Joe Biden.